The PI launchpad: Expanding the base of potential principal investigators across space sciences - Hamden, Erika; New, Michael H.; Pugel, D.E. (Betsy); Liemohn, Michael; Wessen, Randii; Quinn, Richard; Propster, Paul; Petree , Kirsten; Gertsen, Ellen M.; Evans, Paula; Salazar, Nicole Cabrera (Frontiers in Astronomy and Space Sciences, 2022)
The PI Launchpad attempts to provide an entry level explanation of the process of space mission development for new Principal Investigators (PIs). In particular, PI launchpad has a focus on building teams, making partnerships, and science concept maturity for a space mission concept, not necessarily technical or engineering practices. Here we briefly summarize the goals of the PI Launchpad workshops and present some results from the workshops held in 2019 and 2021. The workshop attempts to describe the current process of space mission development (i.e. space-based telescopes and instrument platforms, planetary missions of all types, etc.), covering a wide range of topics that a new PI may need to successfully develop a team and write a proposal. It is not designed to replace real experience but to provide an easily accessible resource for potential PIs who seek to learn more about what it takes to submit a space mission proposal, and what the first steps to take can be. The PI Launchpad was created in response to the high barrier to entry for early career or any scientist who is unfamiliar with mission design. These barriers have been outlined in several recent papers and reports, and are called out in recent space science Decadal reports.